High-speed silicon modulators for the 2 μm wavelength band - Cao, Wei (2019)
The 2 μm wavelength band has become a promising candidate to be the next communication window. We demonstrate high-speed modulators based on a 220 nm silicon-on-insulator platform working at a wavelength of 1950 nm, using the free carrier plasma dispersion effect in silicon. A Mach–Zehnder interferometer modulator and a microring modulator have been characterized. At 1950 nm, the carrier-depletion modulator operates at a data rate of 20 Gbit/s with an extinction ratio of 5.8 dB and insertion loss of 13 dB. The modulation efficiency (V ·L ) is 2.68 V·cm at 4 V reverse bias. The device operation is broadband, and we also characterize its performance at 1550 nm. At 1550 nm, an open eye is obtained at 30 Gbit/s. The difference in bandwidth is caused by the bandwidth limit of the 2 μm measurement setup. We also show a ring modulator paired with a low power integrated driver working in hybrid carrier depletion and injection mode at a data rate of 3 Gbit/s with power consumption of 2.38 pJ/bit in the 2 μm wavelength range. This work is a proof of principle demonstration and paves a route toward a full silicon-based transceiver in the 2 μm window.